Differences in sleep quality and sleep behaviors between the preparation and competition phases in handball athletes - Wiga Nurlatifa Romadhoni; Nasuka Nasuka; Erwin Nizar Priambodo; Duaji Rahadyan Nursantiko (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2026)
Sleep quality and sleep behaviors are essential for athletes’ recovery and performance; however, their variation across competitive phases remains insufficiently understood. This study aimed to examine differences in sleep quality and sleep behaviors between the preparation and competition phases among male handball athletes. A quantitative study with a comparative within-subject design was employed, using repeated measurements collected at two time points and analyzed to identify phase-based changes. The participants were 24 male handball athletes from Semarang City preparing for PORPROV 2023, selected using total sampling. Sleep quality and sleep behaviors were assessed using the Pittsburgh Sleep Quality Index (PSQI) and the Athlete Sleep Behavior Questionnaire (ASBQ). Data were collected during the preparation and competition phases and analyzed using descriptive statistics and paired-sample t-tests. The results showed a significant decline in sleep quality during the competition phase, reflected in higher PSQI scores (2.12 to 2.56; p < 0.05), increased sleep disturbances (3.4 to 4.1; p < 0.05), longer sleep onset latency (43 to 46 minutes; p < 0.05), and a marked rise in late-night exercise (1.3 to 3.6; p < 0.01), along with increased disturbance frequency (1.7 to 2.1 times; p < 0.05). In contrast, changes in sleep duration, stimulant use, and restroom interruptions were not statistically significant. These findings indicate that the competition phase is associated with measurable changes in both physiological and behavioral aspects of sleep and contributes to phase-specific evidence of sleep dynamics in team sports.